AORTODUODENAL FISTULA PRESENTING 17 YEARS AFTER SURGERY FOR ABDOMINAL AORTIC ANEURYSM-CASE REPORT - SHINDO, Manabu; TOMIYAMA, Mitsuhiro; KATO, Hiroyuki; MANASE, Hiroto (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2002)
The subject was a 73-year-old male with a history of artificial prosthesis for an aneurysm of the abdominal aorta at 56 years of age. He was admitted to our hospital for massive hematemesis and melena. Emergency abdominal computed tomography (CT) examinations revealed bilateral femoral artery aneurysm, but there were no false aneurysms at the proximal site of anastomosis with the prosthesis. Emergency endoscopic examination revealed an ulcer in the ascending portion of the duodenum, and the prosthesis was seen exposed at its base. On the basis of these findings, a diagnosis of secondary aortoduodenal fistula was made. At operation, partial dissection of the duodenum containing the ulcer was performed, and the bleeding at the proximal site of anastomosis of the prosthesis was sutured and then reinforced and covered with greater omentum. Because, even long time has passed since artificial vessel replacement for aortic aneurysm had been performed, perforation to the proximal organs might occur, more careful observation seemed important. It is suggested that endoscopic examinations are more useful for diagnosis than CT examinations and are necessary to make for a definite preoperative diagnosis.